Penerapan Bimbingan Kelompok Terhadap Pencapaian Tugas Pekerjaan Bimbingan Sosial Pada Siswa Di SMA Negeri 1 Barru - Anuar, Arman Bin (Universitas Negeri Makassar, 2018)
The problem in this thesis is whether there is influence of the implementation of group guidance to the achievement of social work guidance tasks in adolescents in SMA Negeri 1 Barru? As for the purpose is to know the influence of the implementation of group guidance on the achievement of the task of youth social counseling in SMA Negeri 1 Barru. This research is quantitative research, with population as many as 839 respondents, while the sample is 84 respondents obtained by random sampling technique, while the data collection instruments used are questionnaires and documents, while data analysis techniques using the formula percentage. The result of the research shows that the regression line formed is y = 2.22 + 0.786X while to test the significant effect or not, this research is F test which the result is Fhitung 933,7994 while Ftabel is 3,96. Based on the results of the study it can be concluded that there is a significant influence between the implementation of group guidance on the achievement of social guidance work on SMA Negeri 1 Barru.